menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
H(x) = x2 + 1 k(x) = x – 2 (h + k)(2) = (h – k)(3) = Evaluate 3h(2) + 2k(3) = .
asked
Oct 7, 2023
144k
views
9
votes
H(x) = x2 + 1 k(x) = x – 2
(h + k)(2) =
(h – k)(3) =
Evaluate 3h(2) + 2k(3) =
.
Mathematics
high-school
Schglurps
asked
by
Schglurps
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
9
votes
(h+k) = x^2 + x - 1
so (h+k)(2) assuming it is a function
= 4 + 2 - 1
= 5
(h+k)(3) = 9 + 3 - 1
= 11
3h(2) = 3*(4+1)
= 15
2k(3) = 2*(1) = 2
so 3h(2) + 2k(3) = 15 + 2
= 17
Rrmerugu
answered
Oct 11, 2023
by
Rrmerugu
5.6k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.6m
questions
7.3m
answers
Other Questions
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
(3x1,000,000)+(3x100,000)+(2x100) what is this number written in standard form?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org